Individualized Oral Care Using Photobiomodulation and Tailored Brushing Method in a Patient with Maxillofacial Trauma – A Case Report - Reghunath, Shruthi; Ramesh, Roshni; Kumar, S Santhosh; Sasi, Anoop; Mohamed, Shahana C; Joy, Bilha; Jayasree, Aswathy (UI Scholars Hub, 2025)
Patients who report to the dental outpatient department following maxillofacial trauma often exhibit suboptimal oral hygiene, which is frequently attributed to challenges in sustaining oral care stemming from pain and restricted mouth opening after the injury. This case report aims to provide an individualized protocol of oral care and pain management for patients with maxillofacial trauma. Case report: A treatment protocol combining the Tailored Brushing Method (TBM), a personalized approach for at-home oral hygiene, and photobiomodulation using low-level laser was performed on a 24-year-old patient with maxillofacial trauma and poor oral hygiene. Results: The TBM is successful in achieving good patient adherence to at-home oral hygiene protocols. The results showed that the application of low-level laser soon after the trauma helped in pain control and augmented the patient’s compliance with the necessary procedures. This application was also shown to be effective in healing intraoral soft tissues. Conclusion: This case report highlights the TBM’s success in improving patient compliance and the effect of photobiomodulation in managing pain and enhancing the healing of soft tissues. In the precision periodontics era, this personalized oral care approach will offer significant therapeutic advantages in the management of patients with maxillofacial trauma.